Loss of dopamine phenotype among midbrain neurons in Lesch–Nyhan disease. Issue 1 (20th June 2014) - Göttle, Martin; Prudente, Cecilia N.; Fu, Rong; Sutcliffe, Diane; Pang, Hong; Cooper, Deborah; Veledar, Emir; Glass, Jonathan D.; Gearing, Marla; Visser, Jasper E.; Jinnah, H. A.
<x xml:space="preserve">Abstract</x> Objective Lesch–Nyhan disease (LND) is caused by congenital deficiency of the purine recycling enzyme, hypoxanthine‐guanine phosphoribosyltransferase (HGprt). Affected patients have a peculiar neurobehavioral syndrome linked with reductions of dopamine in the basal ganglia. The purpose of the current studies was to determine the anatomical basis for the reduced dopamine in human brain specimens collected at autopsy. Methods Histopathological studies were conducted using autopsy tissue from 5 LND cases and 6 controls. Specific findings were replicated in brain tissue from an HGprt‐deficient knockout mouse using immunoblots, and in a cell model of HGprt deficiency by flow‐activated cell sorting (FACS). Results Extensive histological studies of the LND brains revealed no signs suggestive of a degenerative process or other consistent abnormalities in any brain region. However, neurons of the substantia nigra from the LND cases showed reduced melanization and reduced immunoreactivity for tyrosine hydroxylase (TH), the rate‐limiting enzyme in dopamine synthesis. In the HGprt‐deficient mouse model, immunohistochemical stains for TH revealed no obvious loss of midbrain dopamine neurons, but quantitative immunoblots revealed reduced TH expression in the striatum. Finally, 10 independent HGprt‐deficient mouse MN9D neuroblastoma lines showed no signs of impaired viability, but FACS revealed significantly reduced TH immunoreactivity compared to the control parent line. Interpretation These results reveal an unusual phenomenon in which the neurochemical phenotype of dopaminergic neurons is not linked with a degenerative process. They suggest an important relationship between purine recycling pathways and the neurochemical integrity of the dopaminergic phenotype. Ann Neurol 2014;76:95–107